Reflections on the COVID moment and life beyond neoliberalism. (February 2022) - Crouch, Colin
The COVID pandemic has demonstrated the weakness of neoliberalism by showing the importance of public services, workers' need for security, and a heightened awareness of collective interdependence. Economic theory recognises the deficiencies of depending on market forces by accepting certain grounds for public intervention, including public and collective goods and negative externalities. Acceptance of the human contribution to climate change has massively increased their importance. The pandemic has had similar effects. The very rich may be able to escape to safe places, but the great mass of us are dependent on the support of each other, often through a mobilisation of resources that only states can organise. While much of the community that was rediscovered during the pandemic was highly local, damage to the climate and the spread of disease cannot be contained within national boundaries; cooperation has to be cross-national. It is therefore incompatible with an obsession with national sovereignty. For Europeans the institutions of the EU are central.